Professor Sonntag's thrilling narrative of the Grinnell exploring expedition to the Arctic ocean : in the years 1853, 1854, and 1855 in search of Sir John Franklin, Under the command of Dr. E.K. Kane - Sonntag, August. (Philadelphia, [etc.] : J.T. Lloyd & co., 1857)
A literary imposture. "I did not write the book, it is a shameful imposition."--Letter from August Sonntag, published in the Philadelphia evening journal, May 19, 1857? Mode of access: Internet.